Jane Addams (1860-1935): Social worker and Peace Builder - James Allen (Social Work & Society, 2008)
The name Jane Addams is typically associated with the Settlement House Movement. As a founder of Hull House, the first settlement house in the United States, Addams worked tirelessly on behalf of the poor and oppressed. Less widely known is the depth of her concern about peace and her efforts as a peace builder. A more careful review, however, of Addams' words and works reveals her passionate commitment to the abolition of war and the restoration of peace. This biographical sketch highlights the breadth and depth of Addams' work both as an advocate for the poor and as an advocate for peace.